Confinement of Magnetic Skyrmions to Corrals of Artificial Surface Pits with Complex Geometries - Matsumoto, Takao; Shibata, Naoya (Frontiers in Physics, 2022)
Magnetic skyrmion is a particle-like swirling spin texture promising for future memory devices. Geometric confinement and artificial control of skyrmions are crucial for such practical applications. In our previous research, we developed a technique to confine skyrmions to simple geometric corrals, such as a rectangle and a triangle, composed of artificial surface pits with nanometer-scale dimensions fabricated by using a focused electron beam. The technique has a potential advantage facilitating more complex geometries, which has not been fully explored yet. Here, we directly visualize skyrmions confined to surface-pit corrals with several complex geometries by using differential phase contrast scanning transmission electron microscopy. We find individual skyrmions are deformed not only in shape but also in size under moderate bias field. We also find deformed skyrmionic spin textures with opposite polarities coexist in the zero-field condition. The present study provides a guidance to confine skyrmions, which should be useful for future applications.